2013
DOI: 10.3329/bjb.v42i1.15865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth regulators on seed germination, seedling growth and some aspects of metabolism of Wheat under allelochemical stress

Abstract: Effects of growth regulators on seed germination, seedling growth and some aspects of metabolism of wheat under allelochemical stress due to oleander and walnut leaf (extract and powder) were investigated. All parameters e.g. seed germination, seedling growth, leaf pigments except the proline content reduced significantly under stress. On the contrary, GA 3 and IBA showed alleviating activities. The alleviation effect of GA 3 was higher than that of IBA .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Previously stimulatory effect of rice hull extracts (Seyyednejad et al, 2010) but inhibitory effect of Jatropha curcas L. (Aburge and Sam, 2010), Dodonaea viscosa (Barkatullah et al, 2010) and oleander and walnut leaf extracts (Unal, 2013) on shoot length of different plants including wheat have been reported. Similarly, our results regarding reduced shoot and seminal root length under leaf extracts are in line with findings of Batlang and Shusho (2007), Singh et al (2009), Sadehgi et al (2010 and Unal (2013) who reported shoot and seminal root suppression of wheat in response to aqueous extracts of different allelopathic plants. Primary effect of allelochemicals may probably be alteration in cell membrane permeability of the target plant which can cause secondary effects such as changes in water and mineral absorptions potentials, changes in pH, enzymatic alterations etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previously stimulatory effect of rice hull extracts (Seyyednejad et al, 2010) but inhibitory effect of Jatropha curcas L. (Aburge and Sam, 2010), Dodonaea viscosa (Barkatullah et al, 2010) and oleander and walnut leaf extracts (Unal, 2013) on shoot length of different plants including wheat have been reported. Similarly, our results regarding reduced shoot and seminal root length under leaf extracts are in line with findings of Batlang and Shusho (2007), Singh et al (2009), Sadehgi et al (2010 and Unal (2013) who reported shoot and seminal root suppression of wheat in response to aqueous extracts of different allelopathic plants. Primary effect of allelochemicals may probably be alteration in cell membrane permeability of the target plant which can cause secondary effects such as changes in water and mineral absorptions potentials, changes in pH, enzymatic alterations etc.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) ise P. undulatum'un yabani hardalın SOD aktivitesini arttırdığını, CAT aktivitesinde ise artma ve azalmalara neden olduğunu saptamıştır. Bitkilerde stres kaynaklı reaktif oksijen türlerinin yok edilmesi için antioksidan enzimlerin üretimi artmaktadır (Apel ve Hirt, 2004;Niakan ve Saberi, 2009;Turkyilmaz Unal, 2013). Allelokimyasallar, konsantrasyona bağlı olarak enzim aktivite artışına veya azalmasına neden olabilmektedir (Farhoudi ve Koreshnejad, 2012;Farhoudi ve Lee, 2013;Romero-Romero ve ark., 2005;Yu ve ark., 2003) Yabancı ot mücadelesinde allelokimyasallardan yararlanma giderek önem kazanmaktadır.…”
Section: Antioksidan Enzim Aktiviteleriunclassified
“…Abiotik ve biyotik streslere karşı gelmede bitkiler süperoksit dismutaz (SOD), katalaz (CAT), askorbat peroksidaz (APX) ve guaiacol peroksidaz (POX) gibi ROS temizleme enzimleriyle donatılmıştır (Caverzan vd., 2016). Allelokimyasalların neden olduğu reaktif oksijen türlerini ortadan kaldırmak amacıyla antioksidan enzimlerin üretiminin arttığı bilinmektedir (Apel ve Hirt, 2004;Niakan ve Saberi, 2008;Niakan vd., 2009;Turkyilmaz, 2013). Özellikle biber bitkisinde yüksek konsantrasyon uygulamalarında antioksidan enzim miktarları artmıştır.…”
Section: İstatistik Analizlerunclassified